2013
DOI: 10.1021/ac400058z
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Electrophoresis–Systematic Evolution of Ligands by Exponential Enrichment Selection of Base- and Sugar-Modified DNA Aptamers: Target Binding Dominated by 2′-O,4′-C-Methylene-Bridged/Locked Nucleic Acid Primer

Abstract: Chemically modified DNA aptamers specific to human α-thrombin were obtained from oligodeoxyribonucleotide (ODN) libraries by using a capillary electrophoresis-systematic evolution of ligands by exponential enrichment (CE-SELEX) method. These libraries contained 2'-O,4'-C-methylene-bridged/linked bicyclic ribonucleotides (B/L nucleotides) in the primer region and/or C5-modified thymidine bearing N(6)-ethyladenine (t) in the nonprimer region. Modified DNA aptamers showed high binding affinities to the target, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 61 publications
2
45
0
Order By: Relevance
“…[56][57][58] Because the band resulted from the recognition of TB by TBA was difficult to be identified by electrophoresis, 59 we employed UV-vis absorption and CD spectra to measure the structure and the binding of hemin and TB to TBA. 60,61,62 As shown in Figure S8A, when mixing TBA and hemin, the typical absorption of hemin became stronger with the absorption peak red shifted from 395 to 404 nm (curve a and b), indicating the formation of a G-quadruplex/hemin structure. 46 The presence of TB caused a further hyperchromicity of the hemin (curve c), which demonstrated that TB promoted binding of hemin in G-quadruplex.…”
Section: Figurementioning
confidence: 95%
See 1 more Smart Citation
“…[56][57][58] Because the band resulted from the recognition of TB by TBA was difficult to be identified by electrophoresis, 59 we employed UV-vis absorption and CD spectra to measure the structure and the binding of hemin and TB to TBA. 60,61,62 As shown in Figure S8A, when mixing TBA and hemin, the typical absorption of hemin became stronger with the absorption peak red shifted from 395 to 404 nm (curve a and b), indicating the formation of a G-quadruplex/hemin structure. 46 The presence of TB caused a further hyperchromicity of the hemin (curve c), which demonstrated that TB promoted binding of hemin in G-quadruplex.…”
Section: Figurementioning
confidence: 95%
“…61 In the presence of TB, the peak intensity of Gquadruplex/hemin increased at 292 nm (curve c). This implied that the pattern of the G-quadruplex structure did not change, but the antiparallel structure became more compact by TB.…”
Section: Figurementioning
confidence: 98%
“…In addition to previously reported selection of ssDNA and RNA aptamers, successful selection of base- and sugar modified DNA aptamers via CE-SELEX has been reported for human α-thrombin. 43 Small size of the starting library in CE-SELEX (~10 12 sequences), a major limitation, has been improved significantly by using a micro free flow electrophoresis (μFFE) device (300-fold, 1.8 10 14 sequences). 44 Isolation of nanomolar affinity aptamers after a single round ( i.e.…”
Section: Selex Methodsmentioning
confidence: 99%
“…Therminator DNA polymerase was used to extend a DNA hairpin primer/template with the modified nucleotides, permitting amplification of the DNA primer-template after selection and resynthesis of the selected TNA aptamer. Kuwahara and co-workers used a mixture of mutant and/or wild type KOD DNA polymerases to “transcribe” and “reverse transcribe” mixed LNA/DNA oligonucleotides during selection of an anti-thrombin aptamer [15,16]. Holliger and co-workers have dramatically expanded the potential of these analogs by evolving a series of TgoT DNA polymerase mutants to better “transcribe” and “reverse transcribe” these modified nucleotides, and they have used them to select HNA aptamers targeting HIV trans-activating response RNA and hen egg lysozyme [17•], a FANA aptamer targeting HIV-1 RT [18], and catalytic nucleic acids containing ANA, FANA, HNA, and CeNA moieties [19].…”
Section: Selex With Modified Rna and Dnamentioning
confidence: 99%